DEEP-DERIVED ENCLAVES (BELONGING TO MIDDLE-LOWER CRUST METAMORPHIC ROCKS) IN THE LIUHE-XIANGDUO AREA, EASTERN TIBET: EVIDENCE FROM PETROGEOCHEMISTRY - Qirong W.; Dewei L.; Jianping Zh.; Jianghai W. (My University, 2006)
Petrological and geochemical studies of deep-derived enclaves from the Liuhe-Xiangduo area, eastern Tibet, showed that the enclaves involve five types of rocks, i. e., garnet diopsidite, garnet amphibolite, garnet hornblendite, amphibolite and hornblendite, whose main mineral assemblages are Grt + Di + Hbl, Grt + P1 + Hbl + Di, Grt + Hbl + P1, P1 + Hbl, and Hb1 + Bt, respectively. The enclaves exhibit typical crystalloblastic texture, and growth zones are well developed in garnet (Grt) in the enclaves. In view of major element geochemistry, the deep-derived enclaves are characterized by high MgO and FeO *, ranging from 12. 00% to 12. 30% and 8. 15% to 10. 94%, respectively. The protolith restoration of metamorphic rocks revealed that the enclaves belong to ortho-metamorphic rocks. The REE abundances vary over a wide range, and ΣREE ranges from 53.39 to 129.04 μg/g. The REE patterns slightly incline toward the HREE side with weak LREE enrichment. The contents of Rb, Sr, and Ba range from 8. 34 to 101μg/g, 165 to 1485 μg/g, and 105 to 721 μg/g, respectively. The primitive mantle-normalized spider diagrams of trace elements show obvious negative Nb, Ta, Zr and Hf anomalies. Sr-Nd isotopic compositions of the enclaves indicated that the potential source of deep-derived enclaves is similar to the depletedmantle, and their (87Sr/86Sr)i ratios vary from 0.706314 to 0.707198, (147Nd/144Nd)i ratios from 0.512947 to 0.513046, and ɛNd(T) values from +7.0 to +9.0, respectively. The potential source of the enclaves is obviously different from the EM2-type mantle from which high-K igneous rocks stemmed (the host rocks), i. e., there is no direct genetic relationship between the enclaves and the host rocks. Deep-derived enclaves in the host rocks belong to mafic xenoliths, and those in the Liuhe-Xiangduo area, eastern Tibet, are some middle-lower crust ortho-metamorphic rocks which were accidentally captured at 20–50 km level by rapidly entrained high-temperature high-K magma, whose source is considered to be located at 50-km depth or so.
Keywords: EASTERN TIBET; LIUHE-XIANGDUO AREA; DEEP-DERIVED ENCLAVE; MIDDLE-LOWER ORTHO-METAMORPHIC ROCK; PETROLOGY; GEOCHEMISTRY